Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T19:28:33+01:00
5a(a-2) + 2a(a+5) =
= 5a²-10a+2a²+10a = 7a²

3(a+2b-3c) - 2(a-2c) + 5(c-b) - (a-b) =
= 3a+6b-9c-2a+4c+5c-5b-a+b = 2b

0,2(5a+10b) - 7(0,1a-b) + a -b =
= a + 2b - 0,7a + 7b+a-b =1,3a +8b
2010-02-25T19:32:38+01:00
5*a*a-2+2*a*a+5
3*a+2*b-3*c-2*a-2*c+5*c-b-*a-b
a+2b-0,7a+7b+a-b=1,3a-6b
2010-02-25T19:34:27+01:00
5a(a-2) + 2a(a+5) = 5a^2- 10a+ 2a^2+10a= 7a^2


3(a+2b-3c) - 2(a-2c) + 5(c-b) - (a-b)= 3a+6b-9c-2a+2c+5c-5b-a+b= 2b-2c


0,2(5a+10b) - 7(0,1a-b) + a -b= a+2b-0,7a+7b+a-b= 1,3a+8b